(untitled) (AYUSHDHARA, 2017)
Menopause is referring to end of reproductive period and starting of aging problems due to lack of ovarian hormones. There is no direct reference found in Ayurveda regarding menopause but Jaravastha can be correlated as Rajonivrittijanya Lakshanas. Rasayana drugs promote the regeneration of Dhatus, intelligence, mental wellbeing, immunity and longevity. So, Rasayana drugs are helpful to decrease aging related problems. Aim: Present study has been planned to evaluate the efficacy of Vayasthapana Gana having Rasayana effect on menopausal syndrome. Materials and methods: Total 18 known cases of menopausal syndrome patients in the age group between 45-55 years, minimum one year after cessation of menses were selected for the study, out of which 16 patients completed the treatment. Vayasthapana Gana Ghanavati 2 tablets (500mg each) were administered twice a day with milk for duration of two months with follow up period of one month. Improvement was monitored as per Menopausal Rating Scale. Result: 13 (81.25%) patients showed mild improvement and 3 (18.75%) patients had moderate improvement. No any significant changes were observed in serum follicle stimulating hormone and serum oestradiol and other laboratory findings. The score of menopausal rating scale was decreased from 27.50 to 14.75 after the treatment. Conclusion: Vayasthapana Gana Ghanavati is safe and effective in the management of menopausal syndrome.